Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

help with both please :)

Help With Both Please class=

Sagot :

Answer: I know two methods of solving both of the sums. One is the method of elimination, the other is method of substitution. You can do any of the given methods which is easier for you. Both methods will be shown below:

                                    Method of Elimination

1) 5x + y = 9       - - - - (i)
  10x - 7y = - 18 - - - - (ii)

eq. (i) multiplied by 2
   10x + 2y = 18  - - - - (i)
   10x - 7y = - 18 - - - - (ii)       {subtraction of eq. (ii) from eq. (i)}
    0   + 9y = 36
              y = 36/9
              y = 4

From eq. (i),
   5x + y = 9
-> 5x + 4 = 9
-> 5x = 9 - 4
->  x = 5/5
-> x = 1

So, x = 1 and y = 4

2) - 4x + 9y = 9 - - - - (i)
      x - 3y = - 6 - - - - (ii)

eq. (ii) multiplied by 3
    - 4x + 9y = 9 - - - - (i)
     3x - 9y  = - 18 - - (ii)        {addition of eq. (ii) and eq. (i)}
      - x + 0 = - 9
              x  =  9

From eq. (ii),
    x - 3y = - 6
->  9 - 3y = - 6
->  - 3y = -6-9
->  y = -15/-3
->  y = 5

So, x = 9 and y = 5

                                Method of Substitution

1) 5x + y = 9       - - - - (i)
  10x - 7y = - 18 - - - - (ii)

eq. (i)

  5x + y = 9
-> y = 9 - 5x

Value of eq. (i) in eq. (ii)
   10x - 7y = - 18
-> 10x - 7(9 - 5x) = - 18
-> 10x - 63 + 35x = - 18
-> 45x = - 18 + 63
-> x = 45/45
-> x =  1

From eq. (i),
   5x + y = 9
-> 5 + y = 9
-> y = 9 - 5
-> y = 4

So, x = 1 and y = 4

2) - 4x + 9y = 9 - - - - (i)
      x - 3y = - 6 - - - - (ii)

eq. (i)
   - 4x + 9y = 9
-> - 4x = 9 - 9y
-> x = (9 - 9y) / -4

Value of eq. (i) in eq. (ii)
      x - 3y = - 6
-> (9 - 9y) / -4  -3y = - 6
-> (9 - 9y + 12y) = - 6 * - 4
-> 3y = 24 - 9
-> y = 15/3
-> y =  5

From eq. (ii)
   x - 3y = - 6
-> x - 3(5) = - 6
-> x - 15 = - 6
-> x = - 6 + 15
-> x = 9

So, x = 9 and y = 5

∩_∩
(„• ֊ •„)♡
┏━∪∪━━━━┓
   hope it helped
┗━━━━━━━┛

Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.